Testing the effects of gene flow on adaptation, fitness, and demography in wild populations - Fitzpatrick, Sarah Warner, author; Funk, W. Chris, advisor; Angeloni, Lisa M., committee member; Angert, Amy L., committee member; Bailey, Larissa L., committee member; Ghalambor, Cameron K., committee member (Colorado State University. Libraries, 2015)
Gene flow should reduce differences among populations, potentially limiting adaptation and population growth. But small populations stand to benefit from gene flow through genetic and demographic factors such as heterosis, added genetic variation, and the contribution of immigrants. Understanding the consequences of gene flow is a longstanding and unresolved challenge in evolutionary biology with important implications for conservation of biodiversity. My dissertation research addresses the importance of gene flow from evolutionary and conservation perspectives. In the first study of my dissertation I characterized natural patterns of gene flow and genetic diversity among remaining populations of Arkansas darters (Etheostoma cragini) in Colorado, an endemic to drying streams of the Great Plains, and a candidate for listing under the US Endangered Species Act. I found low diversity and high isolation, especially among sites with low water availability, highlighting this as a species that might eventually benefit from a well-managed manipulation of gene flow. I then turned to the Trinidadian guppy system to test the effects of gene flow using a model species for studying evolution in natural populations. My work capitalized on a series of introduction experiments that led to gene flow from an originally divergent population into native recipient populations. I was able to characterize neutral genetic variation, phenotypic variation, and population size in two native populations before the onset of gene flow. The goal of my first study using this system was to evaluate the level of gene flow and phenotypic divergence at multiple sites downstream from six introduction sites. I found that traits generally matched expectations for local adaptation despite extensive homogenization by gene flow at neutral loci, suggesting that high gene flow does not necessarily overwhelm selection. I followed up on this study by measuring many of the same traits in a common garden environment before and after gene flow to test whether gene flow caused genetically based changes in traits, and to evaluate the commonly held 'gene flow constrains divergence' hypothesis versus the 'divergence in the face of gene flow' hypothesis. I found that gene flow caused most traits to evolve, but whether those changes constrained adaptation depended on initial conditions of the recipient population. Finally, to link gene flow to changes in fitness and demography I conducted a large-scale capture-mark-recapture survey of two native populations beginning three months prior and following 26 months after upstream introductions took place. I genotyped all individuals from the first 17 months of this study to compare the relative fitness (survival and population growth rate) of native, immigrant, and hybrid guppies. In total this survey spanned 8-10 guppy generations and documented substantial increases in genetic variation and population size that could be attributed to gene flow from the introduction site. As a whole, the results from my research suggest that gene flow, even from a divergent population, can provide major demographic benefits to small populations, without necessarily diminishing locally important traits.
Keywords: evolution; gene flow; population genetics; fitness; adaptation; mark-recapture